Auto-routing algorithm for field-programmable photonic gate arrays - López, Aitor; Pérez, Daniel; DasMahapatra, Prometheus; Capmany, José (Optics express, 2020)
Programmable multipurpose photonic integrated circuits require software routines to make use of their flexible operation as desired. In this work, we propose and demonstrate the use of a modified tree-search algorithm to automatically determine the optimum optical path in a field-programmable photonic gate array (FPPGA), based on end-user specifications, circuit architecture and imperfections in the realized FPPGA arising, for example, from fabrication variations. In such a scenario, the proposed algorithm only requires the hardware topology and the location of the connections of the FPPGA defining the optical path to be programmed. The routine is able to optimize the path over multiple and competing objectives like the overall length, accumulated loss and power consumption. In addition, should any region of the circuit suffer from any potential damage that may affect the device performance, this algorithm is also able to provide basic self-healing and fault-tolerance capabilities by supplying alternative paths through the photonic arrangement.